Decubital Candidiasis Mimicking Molluscum Contagiosum in an Unconscious Patient - Laura Noviani; Suci Widhiati; Harijono Kariosentono; Nurul Hidayati; Vrenda Alia (Universitas Malahayati, 2024)
ABSTRACT Decubital candidiasis is a rare type of candidiasis often found in bedridden patients. Unlike decubital ulcer, it is also characterized with pustules and papules along with erythema, erosions, and scales. This lesion usually develops in the posterior thorax, lumbosacral, and gluteal region. In this case report, a patient was referred to us with generalized papules that was initially thought to be molluscum contagiosum after being admitted to intensive care unit (ICU). Keywords: Decubital Candidiasis, Candidiasis Miliaria, Candidiasis, Bedridden, Molluscum Contagiosum